PENGARUH KEPEMIMPINAN, KEDISIPLINAN, BEBAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH DASAR - -, Sunarso - (Universitas Slamet Riyadi, 2010)
ABSTRACT This research target which will be reached is to (1) Searching empirical evidence there are leadership influence significant, discipline, work load, work motivation to teacher performance (2) Analyzing leadership influence significant, discipline, work load and dominant work motivation to teacher performance Problem of work load need resolving which do not easy to because accounted on work load and executed by teacher have been arranged in expert duty and guidance and function to teacher. Beside learn to be claimed to execute study process which is innovative and is maximal, but having to can finish administration becoming its obligation. Workmanship of Book administration represents authentic evidence to a teacher in executing its duty in class and also outside class. Curriculum not possible to be altered because representing guidance learns in study burden although study very felt by is teacher in study with existing time. Keywords: Leadership, discipline, work load, work motivation, teacher performance